The Analysis of Participant Role in the Jakarta Post Headlines’ Titles - Hella Ayu Setyanida (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2018)
This research aims at describing the roles as in NP construction of the title in the Jakarta Post and describing the denotative and connotative meaning of the title in the Jakarta Post. The research conducted by the writer is descriptive qualitative research. The data of this research are simple declarative sentence of the title in the Jakarta Post online newspaper, while the data source is taken from the Jakarta Post online newspaper published June 2018. The result of this research shows that there are twenty-two patterns that are classified into three roles in the starting sentence. They are 13 locations, 7 agents and 2 experiencers. NPs functioning as agent and experiencer when the type of simple declarative sentence is active sentence, while NPs1 functioning as theme when the type of simple declarative sentence is passive sentence. The writer analyzes the meaning by referring to the denotative and connotative meaning. The denotative meaning is analyzed by paraphrasing or re-construction, while connotative meaning is analyzed by using personal aspect and intercontextuality of the sentence. The result of data analysis in the case of denotative and connotative meaning by using paraphrasing or reconstruction is that the meaning of the titles in the Jakarta Post is more clearly and comprehensive, not only the meaning of the words but also show the aspect of personal and intercontextuality.